A simulation on coevolution between language and multiple cognitive abilities. Issue 1 (29th January 2022) - Gong, Tao; Shuai, Lan; Yang, Xiaolong
Abstract: We propose a coevolution scenario between language and two cognitive abilities, namely shared intentionality and lexical memory, under a conceptual framework that integrates biological evolution of language learners and cultural evolution of communal language among language users. Piggybacking on a well-attested agent-based model on the origin of simple lexicon and constituent word order out of holistic utterances, we demonstrate: (1) once adopted by early hominins to handle preliminary linguistic materials, along with the origin of an evolving communal language having a high mutual understandability among language users, the initially low levels of the two cognitive abilities are boosted and get ratcheted at sufficiently high levels in language users for proficient language learning and use; (2) the socio-cultural environment is indispensable for the coevolution, and natural selection (selecting highly understandable adults to produce offspring), not cultural selection (choosing highly understandable adults to teach offspring), drives the coevolution. This work modifies existing models and theories of coevolution between language and human cognition and clarifies theoretical controversies regarding the roles of natural and cultural selections on language evolution.